0129 Association of Sleep Quality with Serum Lipids in Obese Adults. (27th May 2020) - Mehta, B; Ankita, A; Raghav, P; Chambial, S; Dutt, N
Abstract: Introduction: Sleep disturbances have been associated with metabolic dysregulation and have known to contribute to weight gain, obesity, type II diabetes, and cardiovascular disease risk. Obesity due to sleep fragmentation is mediated by multiple pathways like upregulation of orexin neurons and changes in appetite-regulating hormones like Leptin, Ghrelin, which affect food intake and hedonic feeding. Conversely, body mass index (BMI) is associated with alterations in sleep and with high circulating lipids and incidence of coronary heart disease. We hypothesized that poor sleep quality is associated with an adverse serum lipid profile. Methods: In this cross-sectional study, till date, 27 obese adult participants were recruited after informed consent. The obesity criterion was taken as BMI ≥ 25 kg/m 2 . Anthropometric parameters, waist circumference, neck circumference, hip circumference, and BP were measured. Sleep quality was assessed by the "Pittsburgh Sleep Quality Index" (PSQI) questionnaire. A score of 5 or more was considered to be adverse sleep. The fasting blood sugar and lipid profile of each participant was determined. Results: The average age, BMI and waist circumference of the subjects were 48.96 ±13.9 years, 32.41± 6.18 kg/m 2 and 107.4 ±12.18 cm respectively. The Spearman correlation test revealed a significant correlation between the PSQI scores and triglyceride levels of the participants (p=0.033, r = 0.420). The correlation with BMI (p=0.33, r=0.192), fasting blood sugar (p=0.26, r=0.241), HDL (p=0.27, r = -0.221) and waist circumference (p=0.69, r = -0.082) were not found to be statistically significant. Conclusion: We conclude that high triglyceride levels are associated with poor quality of sleep in adults. Although other biochemical parameters did not show a significant correlation, a greater sample size may give us a clear insight into it. Support: The study is an intramural project supported by AIIMS, Jodhpur.